FIFTEEN YEARS OF THE “STUDENTS FOR CHILDREN” PROGRAM: TRAUMA-INFORMED VOLUNTEERISM AND INTERDISCIPLINARY COLLABORATION IN CHILD PROTECTION - Korinek, Beáta; Zeller, Judit; Kulcsár, Gabriella; Kovács, Patricia; Kondora, Petra (International Journal of Child, Youth and Family Studies, 2025)
The Students for Children program has been running for more than 15 years in Hungary, offering university students an opportunity to engage in child protection work through a trauma-informed, interdisciplinary approach. The program serves a dual purpose: supporting children in specialized care while equipping students with practical experience in working with vulnerable populations. Through structured classroom training, supervised volunteer work, and collaborative partnerships with child protection institutions, the program fosters professional preparedness, ethical engagement, and social responsibility. This paper explores the program’s development, key guidelines, and bridging function of linking disciplines, institutions, and international networks to strengthen child welfare efforts. Insights from student testimonials and micro-research findings illustrate the program’s impact, highlighting its role in promoting trauma-informed care, emotional safety, and sustainable professional engagement.